Beberapa Senyawa Fenol dari Tumbuhan Morus macroura Miq. - Nunuk H Soekamto; Sjamsul Arifin Achmad; Emilio L Ghisalberti; Norio Aimi; Euis Holisotan Hakim; Yana Maolana Syah (Institut Teknologi Bandung, 2003)
Three stilbene derivatives, namely lunularin (1), oxyresveratrol (2), and andalasin A (3), together with 2-arylbenzofuran derivative, moracin M (4), coumarin derivative, umbelliferon (5), and Î²-resolcylaldehyde, were isolated from Morus macroura Miq. (Moraceae), a rare spesies found in West Sumatera and endemic to Indonesia. The structures of all these compounds were elucidated based on physical and spectroscopic data.